Bentuk dan makna kata ganda Bahasa Melayu berdasarkan data korpus - Ismail, Zaidi; Sha’ri, Sharil Nizam; Abdul Aziz, Adi Yasran; Mohd Hanafiah, Halis Azhan (Universiti Putra Malaysia, 2026)
This study examines the forms and meanings of reduplicated words in the Malay language based on corpus data. Reduplication refers to words formed through the repetition of a base word, which are categorised as true reduplications. However, there are also words that resemble true reduplications but cannot be traced back to their original base forms. These are known as pseudo-reduplications, such as sia-sia (in vain), hati-hati (careful), huru-hara (chaos), kucar-kacir (disorder), and seolah-olah (as if). These forms are often confusing because of their similarity to true reduplications. Therefore, this study was conducted to achieve three main objectives: (i) to identify true and pseudo-reduplications; (ii) to analyse and compare true and pseudo-reduplications; and (iii) to summarise the forms and meanings of true reduplications in contrast to pseudo-reduplications. The study employs a qualitative approach using text analysis methods, grounded in the Systemic Grammar Theory and the Componential Meaning Analysis proposed by Omar (1993). Data samples were purposively selected from both true and pseudo-reduplications found in the Dewan Bahasa dan Pustaka (DBP) Corpus Database. The findings indicate that both true and pseudo-reduplications can be classified into four main types: full, rhythmic, affixed, and partial reduplications. Examples include aspek-aspek (aspects), mandi-manda (bathing activities), beramai-ramai (in groups), and gegelung (coil) for true reduplications; as well as anai-anai (termites), serta-merta (immediately), kepura-puraan (pretence), and peparu (lungs) for pseudo-reduplications. This study serves as an important reference for language users, particularly grammar writers, in understanding and classifying reduplicated forms in Malay more accurately.